2014
DOI: 10.1007/s00170-014-6087-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the thermal effects during nanometric cutting process while using nanoscale diamond tools

Abstract: In this paper, large scale molecular dynamics simulations are carried out to investigate the thermal effect on nanometric cutting of copper while using a single tip and a multi-tip nanoscale diamond tool. A new concept of atomistic equivalent temperature is proposed and used to characterize the temperature distribution in the cutting zone. The results show that the cutting heat generated while using a multi-tip tool is larger than that of using a single tip tool. The local temperature is found to be higher at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Similar results were found in niobium single crystals [185] and even amorphous metals [186,187]. Abad et al investigated temperature-dependent size effects on the strength of [111]-oriented tantalum and [100]-oriented tungsten pillars by elevated temperature compression tests [188]. Kaira et al [189] investigated the microscale deformation behavior of bicrystal boundaries in pure tin by the micropillar compression tests and found that Atoms tend to form the side flow region (yellow) and residual region (blue), a before and b after nano-cutting [139] the random angle grain boundaries in the micropillar act as barriers to the dislocation glide causing the strengthening mechanism.…”
Section: Influence Of Ductile Materialssupporting
confidence: 58%
“…Similar results were found in niobium single crystals [185] and even amorphous metals [186,187]. Abad et al investigated temperature-dependent size effects on the strength of [111]-oriented tantalum and [100]-oriented tungsten pillars by elevated temperature compression tests [188]. Kaira et al [189] investigated the microscale deformation behavior of bicrystal boundaries in pure tin by the micropillar compression tests and found that Atoms tend to form the side flow region (yellow) and residual region (blue), a before and b after nano-cutting [139] the random angle grain boundaries in the micropillar act as barriers to the dislocation glide causing the strengthening mechanism.…”
Section: Influence Of Ductile Materialssupporting
confidence: 58%
“…The colour scheme of centro-symmetry parameter (CSP) value [14,23] is indicated in Table 4. The atomistic equivalent temperature [15] was employed to analysis the cutting temperature distributions under different cutting conditions. Table 4.…”
Section: Simulation Setupmentioning
confidence: 99%
“…Recently, the difference of machining nanostructures between using single tip and multi-tip diamond cutting tools has also been reported [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous MD nanometric cutting models were built to emulate the material removal process [10][11][12] and to study the effect of tool geometry on the machined surface quality [13][14][15]. Recently the difference in machining nanostructures between using single tip and multi-tip diamond cutting tools has also been reported [9,16].…”
Section: Introductionmentioning
confidence: 99%